Spatial Analysis of Land Cover and Land Uses in Al-Shoubak District / Ma’an Governorate During the Period 1990-2021 Using Remote Sensing and Geographic Information Systems - Zregat, Dalal (Jordan Journal of Social Sciences, 2024)
This study aims to identify the main types of land cover and land use in Al-Shoubak District/ Ma’an Governorate, and to analyze the spatial and temporal changes in land cover and land use distribution using Geographic Information Systems (GIS) and Remote Sensing (RS) techniques. Various topographic characteristics were derived from the Digital Elevation Model (DEM), obtained from the topographic maps of Al-Shoubak District at a scale of 1:25,000. Landsat satellite images from the years 1990, 2005, and 2021 were also used. The study found that there are four main types of land cover and land use in Al-Shoubak District: built-up areas, agricultural land, barren land, and unused land. The study also revealed changes in land cover and land use between 1990 and 2021, with a change rate of 200% for built-up areas, -84.14% for agricultural land, 10.3% for unused land, and 0.21% for barren land. Additionally, the study highlighted the transformation of each type of land cover and land use.